Pengaruh Faktor Sosial Ekonomi Terhadap Minat Pemuda Desa Modopuro Kecamatan Mojosari di Kawasan Industri Kabupaten Mojokerto Dalam Melakukan Usaha Peternakan Itik - Iga Safita; Siti Azizah (CV. Komunitas Dunia Peternakan, 2024)
The research was conducted to determine the influence of socio economic factors to the interest of youth at Modopuro Village, Mojosari District, Mojokerto Regency in raising ducks. The research was conducted in September - Oktober 2022 in Modopuro Village, Mojosari District, Mojokerto Regency and was done with quantitative method. The population and sample of this study were Modopuro Village youth aged 16-30 years, totaling 92 respondents chosen by the purposive sampling method. The variables of the research is the independent variables (income, family environment, community environment, and social status) and the dependent variables namely youth interest. The data obtained from observation, and questionnaires for respondents. Data analysis in this study used multiple regressions. Variables that have a significant influence to the interest of youth in raising ducks are community environment and social status.